Uma proposta de reformulação do ensino de Língua Portuguesa para a licenciatura em Letras - Língua e Literatura Portuguesa do Parfor/Ufam a partir dos princípios linguísticos e pedagógicos da Educação Linguística - Barbosa, Claudio Sampaio (2019)
This thesis is part of the line of research on Reading, Writing and Teaching of the Portuguese Language. Its theme is the teaching of the Portuguese Language based on the proposals of Linguistics Educational (LE) for the development of students' communicative competence in specific situations marked by the cultural and linguistic pluralism – typical of the Amazon region. Thus, considering the challenge of being a teacher in a university course, in a system of education historically marked by a vicious cycle of changes and lack of political planning, and by the peculiar intercultural relations of the Amazon people – and also from the conception that a curricular proposal should contain the accumulated and known human knowledge in a systemic way –, the following question has been posed for this research: what guiding principles should be included in the proposals of the Pedagogical Project of the Course (PPC), in the academy of Letters for the Portuguese Language and Literature course, of the Parfor/Ufam, considering the diversity of the students of this course? For this reason, based on the hypothesis of the need of updating the PPC to be conformed to the diversity of the Amazonian communities served by the course, the general objective of this thesis is to propose – under the light of Linguistics Education – some linguistic and pedagogical guiding principles for the course of Letters – Parfor/Ufam. In addition, it is also intended to demonstrate that the PPC presents inadequacies for the students' education due to the lack of a linguistic education focused on the Amazonian intercultural contexts. Besides, it presents a proposal of the Portuguese language teaching based on the principles of the historicity of the subject’s language and his linguistic activities, also based on the social context of the verbal interactions, according to an epilingual perspective and to a pedagogy of the ways of teaching and learning. For this, as a theoretical basis, besides the LE, the research is based on the proposals of Textual Linguistics and historical-critical pedagogy. Concerning the methodological procedures, the work is configured as a diagnostic tool that comes true by the adoption of a qualitative exploratory approach. The results have shown the need to reformulate the majored students’ profile in the course and the need for interfaces between the obligatory disciplines with socio-cognitive-interaction approaches. For all of that, the work seeks to contribute to the formation of reflective professionals engaged in the formation of thinking-communicating individuals